Pemilihan medikamen intrakanal antar kunjungan yang rasional - Indrya Kirana Mattulada (Journal of Dentomaxillofacial Science, 2010)
Bacteria and their products play a fundamental role in the initiation, propagation andpersistence of pulpal and periradicular diseases. Consequently one of the major goalsof endodontic treament is to eliminate all bacteria from the root canal space.Elimination of microorganism from infected root canal is a complicated task.Numerous measures have been described to reduce the numbers of root canalmicroorganism, including the use of various instrumentation techniques, irrigationregimens, and intracanal medication. In endodontic treatment, there are severalmedicament used traditionally. They are phenolic, aldehyde, halogen, calciumhydroxide, and antibiotic. The aim of this paper is to discuss about indication,contraindication and effect of each medicament.